Short-term blood pressure variability and brain functional network connectivity in older adults - Isabel J. Sible; Jung Yun Jang; Anna E. Blanken; John Paul M. Alitin; Allie Engstrom; Shubir Dutt; Anisa J. Marshall; Arunima Kapoor; Fatemah Shenasa; Aimée Gaubert; Amy Nguyen; Farrah Ferrer; et al. (NeuroImage: Reports)
Background: Blood pressure variability is increasingly linked with cerebrovascular disease and Alzheimer's disease, independent of mean blood pressure levels. Elevated blood pressure variability is also associated with attenuated cerebrovascular reactivity, which may have implications for functional hyperemia underpinning brain network connectivity. It remains unclear whether blood pressure variability is related to functional network connectivity. We examined relationships between beat-to-beat blood pressure variability and functional connectivity in brain networks vulnerable to aging and Alzheimer's disease. Methods: 53 community-dwelling older adults (mean [SD] age = 69.9 [7.5] years, 62.3% female) without history of dementia or clinical stroke underwent continuous blood pressure monitoring and resting state fMRI scan. Blood pressure variability was calculated as variability independent of mean. Functional connectivity was determined by resting state fMRI for several brain networks: default, salience, dorsal attention, fronto-parietal, and language. Multiple linear regression examined relationships between short-term blood pressure variability and functional network connectivity. Results: Elevated short-term blood pressure variability was associated with lower functional connectivity in the default network (systolic: standardized ß = −0.30 [95% CI -0.59, −0.01], p = .04). There were no significant associations between blood pressure variability and connectivity in other functional networks or between mean blood pressure and functional connectivity in any network. Discussion: Older adults with elevated short-term blood pressure variability exhibit lower resting state functional connectivity in the default network. Findings support the role of blood pressure variability in neurovascular dysfunction and Alzheimer's disease. Blood pressure variability may represent an understudied early vascular risk factor for neurovascular dysfunction relevant to Alzheimer's disease, with potential therapeutic implications.